Mixing Oil and Water? Redrawing the Limits of Contract Freedom After the Criminalization of Usury - Le Guerrier, Catherine (Ottawa Law Review / Revue de droit d’Ottawa, 2023)
Theorists who debate whether private law should remain truly private rarely consider the possibility of a disruptive collision between private law and regulation that would force the former to engage with public policy concerns. This article shows an example of such a collision, which was caused by Parliament’s choice to criminalize the act of agreeing to receive interest at more than 60% per year. Rather than voiding the contracts of sophisticated parties that ran afoul of the prohibition, Canadian common law courts adapted the doctrine of illegality and rules on severance rapidly to allow them to be upheld in part: first, the courts severed the obligation to pay any interest on the loan; next, they used blue-pencil severance to reduce the amount of interest owed; and lastly, they created a new remedy, “notional severance,” to craft a new contract for the parties, effectively making contract law directive rather than facilitative. In the end, notional severance was interpreted restrictively as only allowing lenders to recoup interest at exactly 60% per year. This paper argues that these collective doctrinal changes were haphazard, and compares them to the ways in which the Québec civil law courts responded to the new criminal provision. It also suggests that theories which stress the resemblance and proximity of private law with regulation are best suited to understand this line of jurisprudence, through which judges made the contract law directive to assert a competing vision of freedom of contract, rather than deferring to Parliament’s view.